Association between cardiometabolic index and self-reported symptoms of obstructive sleep apnea: a cross-sectional study - Mingyue Cui; Xianchao Xiao; Xue Zhao; Xiaokun Gang; Guixia Wang (Scientific Reports)
Abstract The Cardiometabolic Index (CMI) is a new indicator of visceral fat distribution and dysfunction that can be calculated using lipid parameters, waist circumference, and height. The relationship between CMI and Obstructive Sleep Apnea (OSA) remains unclear. This cross-sectional study explored the association between CMI and OSA using nationally representative data from The National Health and Nutrition Examination Survey database, spanning the periods from 2005 to 2008 and 2015 to 2018. OSA was self-reported based on questionnaire responses. Weighted logistic regression and restricted cubic splines were used to investigate the relationship between CMI and OSA. In addition, subgroup analyses and interaction tests were performed to study the robustness of the association across different populations. Finally, a receiver operating characteristic curve (ROC) was used to determine the predictive power of the index for the OSA. A total of 8460 participants were enrolled in the study. In the fully adjusted model, multivariate regression revealed a significant relationship between CMI and OSA (OR = 1.75, 95% CI 1.46–2.10). Interaction tests, revealed no significant effects of age, sex, body mass index, and race on the relationship between CMI and OSA. The area under the curve (AUC) of the ROC curve was 0.605, indicating that CMI has a predictive value for the OSA. This study provides evidence that CMI is associated with OSA in the adult population of the United States. CMI may be an important predictor of OSA, which provides a new perspective for the future assessment and treatment of individuals with odds of OSA.